2011
DOI: 10.1021/nl202390s
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon Dynamics in Colloidal Cu2–xSe Nanocrystals

Abstract: The optical response of metallic nanostructures after intense excitation with femtosecond-laser pulses has recently attracted increasing attention: such response is dominated by ultrafast electron-phonon coupling and offers the possibility to achieve optical modulation with unprecedented terahertz bandwidth. In addition to noble metal nanoparticles, efforts have been made in recent years to synthesize heavily doped semiconductor nanocrystals so as to achieve a plasmonic behavior with spectrally tunable feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
200
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(230 citation statements)
references
References 44 publications
(130 reference statements)
25
200
0
1
Order By: Relevance
“…12) exhibit a common general trend with two well separated temporal dynamics: a short--time dynamics, on the time--scale of few ps, and a long--time dynamics, on the time scale of hundred ps. These distinct temporal behaviours have been attributed to the dynamical features of the two fundamental processes of carrier--phonon interaction and phonon--phonon interaction respectively [52,69], similarly to what observed in gold and silver nanoparticles. Actually, when the pump pulse is in the infrared region of the spectrum, the initial Fermi distribution of free carriers of the systems is strongly perturbed by pump absorption; the pump pulse creates energetic carriers that are ments; 19 this material is also blue, but the l absorption has not been discussed in the emonstrate in this communication that (W 24 O 68 ) can support strong LSPRs and account for a strong absorption feature ed edge of the visible to the near-IR (NIR).…”
Section: Ultrafast Plasmon Response In Semiconductor Nanocrystalsmentioning
confidence: 64%
“…12) exhibit a common general trend with two well separated temporal dynamics: a short--time dynamics, on the time--scale of few ps, and a long--time dynamics, on the time scale of hundred ps. These distinct temporal behaviours have been attributed to the dynamical features of the two fundamental processes of carrier--phonon interaction and phonon--phonon interaction respectively [52,69], similarly to what observed in gold and silver nanoparticles. Actually, when the pump pulse is in the infrared region of the spectrum, the initial Fermi distribution of free carriers of the systems is strongly perturbed by pump absorption; the pump pulse creates energetic carriers that are ments; 19 this material is also blue, but the l absorption has not been discussed in the emonstrate in this communication that (W 24 O 68 ) can support strong LSPRs and account for a strong absorption feature ed edge of the visible to the near-IR (NIR).…”
Section: Ultrafast Plasmon Response In Semiconductor Nanocrystalsmentioning
confidence: 64%
“…Therefore, it is not surprising that they could also be modelled by the TTM. 74 The results by Scotognella et al 22 By means of broadband pump-probe spectroscopy they found that the shape and the relaxation dynamics of the LSPR have strong analogies with those of noble metal NCs. 74 Broadly speaking, when the photon energy of the pump beam is below the onset of interband transitions, the optical properties are dominated by intra-band transitions and the interband ones only contribute with an offset to the dielectric permittivity.…”
Section: 7174-76mentioning
confidence: 99%
“…6c and d). 74 This model was initially developed in order to rationalize the transient optical response of metals, after the absorption of sub-picosecond laser pulses, 74 and it considers electrons and phonons as two thermal reservoirs in thermodynamic equilibrium. Although this assumption is not strictly valid until the electrons have reached internal equilibrium (about 200 fs after laser excitation) the TTM could qualitatively reproduce the transient optical response of metal NCs.…”
Section: 7174-76mentioning
confidence: 99%
See 1 more Smart Citation
“…[8,9] Others have shown similar LSPRs in nanocrystals of copper(I) selenide and copper(I) telluride. [10][11][12][13][14][15][16] LSPR tunability by variation of the copper vacancy concentration has also been demonstrated by the Alivisatos and Manna groups: the greater the vacancy concentration, the higher the LSPR frequency. [9,10] Metal nanoparticles do not possess such tunability, as their free carrier concentrations are large and difficult to perturb appreciably.…”
mentioning
confidence: 69%